A statistical assessment of tourism development disparities at the district level: The case of Serbia - Stamenković, Milan; Milanović, Marina (Hotel and Tourism Management, 2023)
Tourism is a sector of immense importance and its advancement plays a crucial role in improving national and promoting balanced regional socio-economic development. This study presents a complex multivariate methodological approach for categorization of 25 districts in Serbia into internally-more similar and externally-more dissimilar clusters by implementing hierarchical agglomerative clustering procedure and analysis of present interdependencies between selected indicators of tourism demand. The statistical validity and quality of the extracted optimal clustering structure are evaluated and confirmed based on the adequate optimality criteria and corresponding results of the non-hierarchical clustering procedure. The proposed categorization of districts clearly and unambiguously confirms the presence of significant tourism development asymmetries between NUTS 3 territories in Serbia, and the existence of intra-regional tourism activity polarization with the developed east and south-west (including the city of Belgrade) on the one end of the spectrum and the less developed north and central areas of Serbia.